Efforts of the Madiun Police Satreskrim in Law Enforcement of Silat College Conflicts in Madiun District to Realize Conducive Public Order - Pasaribu, Steven Satria (Advances in Police Science Research Journal, 2024)
Pencak silat is one sport that has many enthusiasts in Madiun Regency. The number of pencak silat schools in Madiun Regency has led to disputes and conflicts accompanied by physical and psychological violence. There were 7 conflicts accompanied by violence throughout 2023. Therefore, law enforcement is needed in conflicts between martial arts schools in Madiun Regency. This research uses a qualitative approach with a case study method. This research uses Routine Activities Theory, Management Theory, Operational Management Function Theory, and Law Enforcement Theory which are accompanied by the Concept of Investigation, the Concept of Crime, the Concept of Legal Sociology, and the Concept of Conflict. The results showed that the Criminal Investigation Unit’s efforts in enforcing the law in conflicts between silat organizations in the form of violence against minors were controlling silat monuments, cyber patrols, community approaches, and implementing the "kring reserse" program. Legal factors that influence law enforcement are article 170 of the Criminal Code, the ability to reveal criminal acts, prosecute legally, and try a criminal offense. Other influencing factors are socio-cultural, facilities and infrastructure, community values, level of education and legal awareness, community participation, economic and social conditions, and trust in the legal system. Based on the results of the above research, the researcher recommends the procurement of facilities and infrastructure, optimization of the "kring reserse" program, as well as intensive partnership approaches and fostering towards silat college leaders.